Comparing sitting time between male and female undergraduate students during weekdays and weekends - Juren, Yohana Unyang; Soh, Kim Geok; Soh, Kim Lam; Ong, Swee Leong; M. K., Siswantoyo; Sunardi, Jaka (Ubiquity Press, 2020)
The purpose of this study was to evaluate the total daily sitting time for male and female undergraduate students and to compare their daily sitting time between weekdays and weekends. A sample of 375 participants responded to the Sedentary Behaviour Questionnaires (SBQ) survey. T-test was used to analyse the differences in sitting time between genders, while multivariate analysis of variance (MANOVA) was performed to investigate the gender differences in the sitting time between weekdays and weekends. The results showed that female undergraduate have a longer daily sitting time (M=9.64 hours/day, SD=30.302) as compared to the male undergraduate (M=9.46 hours/day, SD=31.296). However, there was no significant difference reported between sitting time for both genders (t=1.379, p= 0.169, p>0.05). Higher total sitting time on weekdays and weekends were also reported by female undergraduate students as compared the male undergraduate students. Similarly, no significant findings were also reported between genders during weekdays and weekends. The reported F-value was F(2,375)=1.7, P=0.05: Wikls’ Lambda=.99; partial eta squared=0.007. Prolong durations of daily sitting time (more then 6 hours daily) is associated with higher rate of chronic diseases and premature death especially among working adults. Hence, undergraduates who are future workforce replacements need to be encouraged to be active and not sit too long during their study years. Good habits such as completing their tasks while standing and to break the prolonged sitting patterns with slight movements should be inculated in their daily routines. This can help them to reduce the risk of being sedentary by sitting too much and too long in a day.